Schimke immunoosseous dysplasia: an ultra-rare disease. a 20-year case series from the tertiary hospital in the Czech Republic - Zieg, Jakub; Bezdíčka, Martin; Němčíková, Michaela; Balaščáková, Miroslava; Suková, Martina; Štěrbová, Katalin; Vondrák, Karel; Dušek, Jiří; Křepelová, Anna (Italian journal of pediatrics, 2023)
BACKGROUND: Schimke immunoosseous dysplasia (SIOD) is an ultra-rare inherited disease affecting many organ systems. Spondyloepiphyseal dysplasia, T-cell immunodeficiency and steroid resistant nephrotic syndrome are the main symptoms of this disease. CASE PRESENTATION: We aimed to characterize the clinical, pathological and genetic features of SIOD patients received at tertiary Pediatric Nephrology Center, University Hospital Motol, Prague, Czech Republic during the period 2001-2021. The mean age at diagnosis was 21 months (range 18-48 months). All patients presented with growth failure, nephropathy and immunodeficiency. Infections and neurologic complications were present in most of the affected children during the course of the disease. CONCLUSIONS: Although SIOD is a disease characterized by specific features, the individual phenotype may differ. Neurologic signs can severely affect the quality of life; the view on the management of SIOD is not uniform. Currently, new therapeutic methods are required.
Keywords: centra terciární péče; Tertiary Care Centers; Nephrotic Syndrome; nefrotický syndrom; syndromy imunologické nedostatečnosti; Humans; Osteochondrodysplasias; Česká republika; lidé; Rare Diseases; vzácné nemoci; Czech Republic; osteochondrodysplazie; kvalita života; Quality of Life; Immunologic Deficiency Syndromes